Ghost wars : the secret history of the CIA, Afghanistan, and bin Laden, from the Soviet invasion to September 10, 2001 /: the secret history of the CIA, Afghanistan, and bin Laden, from the Soviet invasion to September 10, 2001. (2005) - Unknown
No abstract available